Implementación de musicoterapia como tratamiento coadyuvante en la recuperación post quirúrgica en perras (canis familiaris) sometidas a ovariosalpingohisterectomia - Muñoz Ordoñez, María Paula (2016)
This research was prepared in the ESPAM-MFL clinic, the application of music therapy as adjuvant treatment in the postsurgical recovery was evaluated, Twenty (20) crossbred dogs were used under ovary salpingohysterectomy with an average weight of fourteen (14) kg, ten (10) receive music therapy and the remaining ten (10) do not receive music therapy, as indicators we used: pain measurement using the modified scale of Melbourne and Glasgow, pheart and respiratory rate , weight gain , feed intake and healing time to treatment to the control groups . both controlled groups of dogs were fed with the same type of food, and food was given every 6 hours.The treatments lasted seven (7) days in each experimental unit, a design group comparison was performed, therefore we obtained the results described below in the treatment group : 1,49 in the variable of pain, a value of 20.85 rpm in respiratory rate , 103.35 bpm in heart rate and 1.98 % of inflammation in somatic concerning the skin condition, feed intake 402,66 g. The results of the control group are 6.82 in variable pain, a value of 28.28 rpm in respiratory rate, 105.09 bpm in heart rate and 2.14 % of inflammation, feed intake 357,69 g. These results demonstrate that the post-surgical music therapy positively influences the patient's recovery to have a highly significant difference in reducing pain and healing time.